Feminist Therapy with Ethnic Minority Women - Sieber, Jindra A. (Canadian Journal of Counselling and Psychotherapy, 2011)
The central thesis of this paper is that feminist assumptions about the nature, process, and goals of therapy make feminist counselling a particularly effective approach for women from diverse racial and cultural backgrounds. The feminist interpretation of women's problems from social, political, and economic perspectives is considered to be particularly relevant to the experiences and realities of immigrant and ethnic-minority women. Similarly, the emphases in feminist therapy on empowering women, on self-direction and personal autonomy, on flexibility in gender roles and on equalization of power in male/ female relationships are considered to be important issues for women belonging to racial ethnic minorities.